Unmet healthcare needs and the local extinction index: an analysis of regional disparities impacting South Korea’s older adults - Kwon, Younggyu; Sohn, Minsung; Choi, Mankyu (Frontiers in Public Health, 2024)
Background: This study examines the factors affecting unmet healthcare experiences by integrating individual-and community-level extinction indices. Methods: Using spatial autocorrelation and multilevel modeling, the study utilizes data from the Community Health Survey and Statistics Korea for 218 local government regions from 2018 to 2019. Results: The analysis identifies significant clustering, particularly in non-metropolitan regions with a higher local extinction index. At the individual level, some factors affect unmet medical needs, and unmet healthcare needs increase as the local extinction index at the community level increases. Conclusion: The findings underscore the need for strategic efforts to enhance regional healthcare accessibility, particularly for vulnerable populations and local infrastructure development.